EEG-responses to mood induction interact with seasonality and age - Höller, Yvonne; Jónsdóttir, Sara Teresa; Hannesdóttir, Anna Hjálmveig; Ólafsson, Ragnar Pétur (Frontiers in Psychiatry, 2022)
Seasonality is operationalized as seasonal variation in mood, appetite, weight, sleep, energy, and socializing. The EEG is suggested as a potential diagnostic and prognostic biomarker for seasonal affective disorder. Importantly, both EEG biomarkers and seasonality interact with age. Inducing sad mood to assess cognitive vulnerability was suggested to improve the predictive value of summer assessments for winter depression. However, no EEG studies have been conducted on induced sad mood in relation to seasonality, and no studies so far have controlled for age. We recorded EEG and calculated bandpower in 114 participants during rest and during induced {sad} mood in summer. Participants were grouped based on the seasonal pattern assessment questionnaire (SPAQ) and age. Participants with high seasonality showed significantly larger changes in EEG power from rest to sad mood induction, specifically in the alpha frequency range (p=.027), compared to participants with low seasonality. Furthermore, seasonality interacted significantly with age (p<.001), with lower activity in high- seasonality individuals over 50 years but the opposite pattern in individuals up to 50 years. Effects of sad mood induction on brain activity are related to seasonality and should therefore be examined as potential predicting biomarkers for {seasonal affective disorder} in longitudinal studies. Future studies should control for age as a confounding factor, and more studies are needed to elaborate on the characteristics of EEG biomarkers in participants above 50 years.